KARSH : "... the heart and the mind are the true lens of the camera.". - Enyeart, James (Kansas : The University of Kansas Museum of Art, 1971)
Photos of Albers, Josef ; Braque, Georges ; Calder, Alexander ; Chagall, Marc ; Ernst, Max ; Gabo, Naum ; Giacometti, Alberto ; Gottlieb, Adolph ; Lipchitz, Jacques ; Marini, Marino ; Manzu, Giacomo ; Miro, Joan ; Moore, henry ; O'Keeffe, Georgia ; Picasso, Pablo ; Ray, Man ; Riopelle, Jean-Paul ; Shahn, Ben ; Soulages, Pierre ; Steichen, Edward
Yousuf Karsh, The University of Kansas Museum of Art, Kansas, 1971
Engels
kunstcatalogus